2019
DOI: 10.1111/epi.16280
|View full text |Cite
|
Sign up to set email alerts
|

Lower myelin‐water content of the frontal lobe in childhood absence epilepsy

Abstract: Objective The frontal lobe in childhood absence epilepsy (CAE) might be affected due to the suggested involvement of the frontal lobe during absence seizures and reports on attentional deficits. Previously, subtle white matter abnormalities have been reported in CAE. However, the impact of one of the most characteristic components of the white matter, the myelin content, remains underdetermined. Therefore, this study investigated whether the myelin content in frontal areas is adversely affected in CAE compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Conversely, previous studies have indicated that neurological disorders associated with abnormal myelin content are accompanied by a higher susceptibility to epileptic seizures [ 60 63 ]. Several studies have indicated that epilepsy is also associated with myelin abnormalities [ 64 – 69 ]. Oligodendrocytes also control potassium accumulation in white matter and seizure susceptibility [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, previous studies have indicated that neurological disorders associated with abnormal myelin content are accompanied by a higher susceptibility to epileptic seizures [ 60 63 ]. Several studies have indicated that epilepsy is also associated with myelin abnormalities [ 64 – 69 ]. Oligodendrocytes also control potassium accumulation in white matter and seizure susceptibility [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the cortex during absence seizures in CAE has been reported in many studies ( Tenney et al, 2013 ; Miao et al, 2014a ; Tang et al, 2016 ; Jun et al, 2019 ). Moreover, cortical impairment has also been reported even in the interictal period ( Xiang et al, 2015b ; Qiu et al, 2016 ; Drenthen et al, 2019 ). Previous reports on source changes in the pre-ictal period have demonstrated that SWDs built up gradually rather than occurring suddenly and that the cortex played a leading role in the initiation of absence seizures ( Gupta et al, 2011 ; Jacobs-Brichford et al, 2014 ; Wu et al, 2017b ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using diffusion tensor imaging have observed widespread microstructural organizational changes, such as reduced fractional anisotropy (FA), which is possibly linked to myelination alterations [27]. Previous work has reported aberrant myelin content in children with epilepsy [28]. Moreover, a recent review also suggested a relationship between pathophysiology of epilepsy and myelin abnormalities [29].…”
Section: Discussionmentioning
confidence: 99%